Atomic-level investigation of interface structure in Ni-Al multilayer system: molecular dynamics simulation - Lee, SG; Kim, SP; Lee, KR; Chung, YC (ELSEVIER, 2005)
In the present work, we investigated deposition behavior of atomic-level interface and surface structure when Ni atoms were deposited on A1(0 0 1) substrate according to substrate temperature and adatom incident energy. In spite of low adatom incident energy of 0.1 eV at room temperature, Ni-Al intermixing occurred actively at the interface and NiAl (B2) and Ni3Al(L1(2)) were found in the interface region. It is found that the interface structure was strongly dependent on the substrate temperature and the adatom incident energy. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: GROWTH; AU; CO